Differences in movement speed before and after a split-step between professional and junior tennis players - Filipcic, A.; Leskosek, B.; Munivrana, G.; Ochiana, G.; Filipcic, T. (Journal of Human Kinetics, 2017)
This study investigated tennis players` speed before, during and after the split-step, deceleration before and acceleration after the split-step in four different stroke groups in three age categories. Seven male professional, eleven male and ten female junior tennis players were recorded with video cameras at official tournaments. Using the SAGIT system, we gathered data on 8,545 split-steps. Tennis players performed a split-step in 82.9% of cases. A tennis player`s speed, deceleration and acceleration were measured 0.2 s before and after the split-step. Differences between categories and stroke groups for each of the five variables were analyzed with a two-way ANOVA. The differences between the groups of players were generally much higher in the speed before, during and after the split-step than in the deceleration before and acceleration after the split-step. Most of these differences were observed between the various stroke groups. These results suggest that players use three types of movement while performing a split-step. In the first type, which is typical of serving and returning, the speed before, during and after the split-step is lower (0.55 to 1.2 m/s). The second type of movement is characteristic of baseline strokes where tennis players achieve higher speed than in the first type (0.7 to 1.66 m/s). The third type occurs in strokes where a tennis player is moving or already at the net (0.78 to 1.9 m/s). Movement in tennis is an area that requires constant development in terms of designing and upgrading movement patterns, increasing speed and practice in specific game situations.